Dynamic modeling of power network-integrated wind turbine - Awalin, Lilik J.; Syahirah, Abd Halim; Syahiman, .; Nor Azuana, Ramli; Naidu, Kanendra; Bazilah, Ismail; Wani, Rosli; Ibrahim, Ali (SAGE Publications, 2022)
This paper presents the performance investigation of voltage and current for dynamic model of the wind turbine. In this study, the various numbers of wind turbine speed are applied in the simulation. This treatment is intended to see how much influence the turbine speed has on the voltage and current output. IEEE 14 bus system is integrated to the wind turbine in order to observe the impact of on-grid connection to the voltage and current performance. How to model wind turbine in PSCAD simulation software also discussed in this paper. The detail of supporting components in designing a wind turbine system and their functions are also explained. Several values of turbine speed are also considered in this paper as a study material in seeing the performance of wind turbines. The relationship between wind speed and pitch angle will also be discussed to ensure that the wind turbine is not damaged. In order to prove the accuracy of the simulation model, the obtained measurement generation of active power from the wind turbine is matched with the manual calculation. Based on the various wind speed values that have been tested, this can be the basis for the application of wind turbine (renewable energy) design development for further research.